The Effect of an Educational Intervention Based on the PRECEDE Model on Quality of Life Improvement in the Elderly Afiliated With Tehran Culture House for the Aged- 2009 - habibeh Matin; Mohammad Eshagh Afkari; Mohammad Hosein Taghdisi (Iranian Association of Health Education and Health Promotion, 2013)
Background: The population of the aged [people] is increasing in all parts of the world even in developing countries. The increase of the number of the aged has created an international trend to increase the quality of life for them. The purpose of performing this project is to study the impact of educational interference based on PRECEDE model in promoting the quality of l ife for t he aged. Methods: This semi-empirical research was performed on 54 aged people who were under the coverage of Tehran Cultural House for the Aged in 2009. The aged people were put in two groups of test and control by using the method of continuous sampling. For educational sampling, the designed questionnaire based on PRECEDE model under the name of PRECEDE model and based on the components of PRECEDE theory were used. In order to assess the quality of life, the questionnaire of the quality of life standard of the World Health Organization (WHO) was used and the quality of life of the aged people in two groups before and after one month from the educational interference was evaluated. Results: The average total score of the components of PRECEDE model including predisposing factors (awareness and attitude), enabling factor (skills), reinforcing factors (personal satisfaction and encouragement by companions), behavioral factors (healthy behaviors) in the test group changed as compared with the control group w ith a p l ess than 0.05. Consequently, opposite to the group control, the quality of life of the aged people of test group showed a meaningful difference before and after educational interference with a p quality less than 0.05. Conclusion: It seems it will be possible to increase the quality of life of the aged with educational interference through PRECEDE model.